VEGF-loaded graphene oxide as theranostics for multi-modality imaging-monitored targeting therapeutic angiogenesis of ischemic muscle - Sun, Zhongchan (Nanoscale, 2013)
Herein we report the design and synthesis of multifunctional VEGF-loaded IR800-conjugated graphene oxide (GO-IR800-VEGF) for multi-modality imaging-monitored therapeutic angiogenesis of ischemic muscle. The as-prepared GO-IR800-VEGF positively targets VEGF receptors, maintains an elevated level of VEGF in ischemic tissues for a prolonged time, and finally leads to remarkable therapeutic angiogenesis of ischemic muscle. Although more efforts are required to further understand the in vivo behaviors and the long-term toxicology of GO, our work demonstrates the success of using GO for efficient VEGF delivery in vivo by intravenous administration and suggests the great promise of using graphene oxide in theranostic applications for treating ischemic disease.